PREPARING STUDENTS AND BIOMETRICS EXPERTS - HAMBALÍK, Alexander; MARÁK, Pavol (Trends in education, 2019)
This contribution provides readers with information about the experience we have gained during an extensive period of development of the special system supporting research and training of students especially in the field of biometrics. This system finds its applications where one needs to employ technologies for parallel task processing using multi-core CPUs, GPUs and fast network connection. It has a unique support for fingerprint recognition, however its hardware and software equipment is designed for multiple purposes so it could be used in different areas of research and education. It adaptively employs all technical and technological possibilities for fast and accurate processing of static images (e.g. fingerprints) or other, more demanding tasks. The hardware also supports video processing. Besides this, it partly allows to solve tasks that are commonly performed during expertise without the need of highly trained professional. Thanks to a powerful GPU that allows fast execution of parallel processes, it can be used in development of optimized encryption techniques suitable for a post-quantum cryptography.
Keywords: preparation of students; experts; specialists; special areas of teaching; biometrics; dactyloscopy; postquant cryptography; unique expert system; expanded area of minutiae